SCOTUS 2024
VIII, 162 p. 2 illus.
Keywords: Each year, the Supreme Court of the United States announces new rulings with deep consequences for our lives. This seventh volume in Palgrave’s SCOTUS Decisions series explains and contextualizes the landmark cases of the US Supreme Court in the term ending 2024. With a close look at cases involving key issues and debates in American politics and society, SCOTUS 2024 tackles the Court's rulings on ballot access, executive immunity, access to mifepristone, funding of the Consumer Financial Protection Bureau, the Equal Protection clause and state redistricting, the Securities and Exchange Commission's ability to levy civil penalties, the power of federal agencies to interpret the laws they administer, the the Environmental Protection Agency's ability to reduce air pollution from power plants, and more. Written by notable scholars in political science and law, the chapters in SCOTUS 2024 present the details of each ruling, its meaning for constitutional debate, and its impact on public policy or partisan politics. Finally, SCOTUS 2024 analyzes ethics scandals on the Court and charts its shifts in ideology. Howard Schweber is Professor Emeritus of Political Science and an affiliate faculty member of the Law School at the University of Wisconsin-Madison. He is the author or editor of six books and the editor of Constitutional Studies.